Implementation of Simple Additive Weighting Method in the Best Lecturer Selection Application - Hendra Effendi; Deri Syabirin; Muhammad Oldy Syahputra (SISFOTENIKA, 2021)
The best lecturer is a form of appreciation that can be given by universities to their lecturers who have carried out the threefold missions of Higher Education (implementing education and teaching, carrying out research and developing science, and carrying out community service) well. This research was conducted at XYZ University Palembang with the aim of developing a web-based application for selecting the best lecturers by applying the Simple Additive Weighting decision-making method. The criteria used are functional position, rank or class, education, length of teaching, number of seminars attended, number of studies, number of published journals and number of community service activities. The software development method used is the prototype method. From the results of the tests carried out, it is known that this application can work and function properly and correctly with a calculation accuracy rate of 100% obtained from comparing the results of calculations manually with the results of application calculations. For further research, it is better to increase the number of criteria used and apply certain methods to determine the weight of the criteria. In addition, it can also make comparisons with other calculation methods in order to find out which method is better in determining the best lecturer.